Money compared with brains - Houghton, Mayme Amelia (My University, 1891)
Introduction: Some are born great, some achieve greatness and some have greatness thrust upon them.” Every person seems to have a different opinion of greatness. Some have the idea that a millionaire is a great person, others that a man of brains is the greater person. Now let us consider this matter and by contrasting the good done by the man of money, and the good done by the man of brains, settle to our own satisfaction, which ones greatness we most admire and would prefer. First it will be necessary for us to make a few suppositious in regard to these men. We will suppose that one is a man of extraordinary means, possessing the brains of an ordinary business person. That the other is a very gifted and brilliant sort of a person, who wins his place in the world by the use and products of his brain. Finally we will suppose that both are equally moral, have the same desire to do good, move in the same sphere in life, and that both have the same length of time in which to work.
Citation: Houghton, Mayme Amelia. Money compared with brains. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Education; Money; Intelligence; Class; Sociology; Theses; Manuscripts (documents)